Experimental investigation of a multicylinder unmodified diesel engine performance, emission, and heat loss characteristics using different biodiesel blends: Rollout of B10 in Malaysia - Abedin, M. J.; Masjuki, Haji Hassan; Kalam, M. A.; Varman, Mahendra; Arbab, M. I.; Rizwanul Fattah, I. M.; Masum, B. M. (Hindawi Publishing Corporation, 2014)
This paper deals with the performance and emission analysis of a multicylinder diesel engine using biodiesel along with an in-depth analysis of the engine heat losses in different subsystems followed by the energy balance of all the energy flows from the engine. Energy balance analysis allows the designer to appraise the internal energy variations of a thermodynamic system as a function of ‘‘energy flows’’ across the control volume as work or heat and also the enthalpies associated with the energy flows which are passing through these boundaries. Palm and coconut are the two most potential biodiesel feed stocks in this part of the world. The investigation was conducted in a four-cylinder diesel engine fuelled with 10% and 20% blends of palm and coconut biodiesels and compared with B5 at full load condition and in the speed range of 1000 to 4000 RPM. Among the all tested blends, palm blends seemed more promising in terms of engine performance, emission, and heat losses. The influence of heat losses on engine performance and emission has been discussed thoroughly in this paper.